(untitled) (Biological Sciences - PJSIR, 2022)
This paper presents an in depth analysis of geospatial characteristics of water and soil parameters and its impact on herbs productivity. The study area considered for this research was Botanical Garden, University of the Punjab, Lahore Pakistan. Eleven soil samples and six water samples were collected from eleven sections and six sections of botanical garden respectively. Seven water parameters EC, Ca, Mg, Na, CO3, HCO3 and Cl were studied, while for soil EC, pH, organic matter, K and P were examined. Interpolation maps were formed to show the spatial pattern of the selected water parameters and graphical representation was done for soil parameters’ analysis. Directional distributional ellipse (GIS statistical analysis) was performed to show the distribution of soil and water parameters and no abnormalities were found in the results which indicates that the soil and water is suitable for the productivity of plants and herbs found in the garden. Keywords: